Triply degenerate nodal line and tunable contracted-drumhead surface state in a tight-binding model - Wang, Yi-Ru; Liu, Gui-Bin (Frontiers in Physics, 2023)
The study of topological semimetals has been extended to more general topological nodal systems such as metamaterials and artificial periodic structures. Among various nodal structures, triply degenerate nodal line (TDNL) is rare and hence lack of attention. In this work, we have proposed a simple tight-binding model which hosts a topological non-trivial TDNL. This TDNL not only has the drumhead surface states as usual nodal line systems, but also has surface states which form a contracted-drumhead shape. And the shape and area of this contracted-drumhead can be tuned by the hopping parameters of the model. This provides an effective way to modulate surface states as well as their density of states, which can be important in future applications of topological nodal systems.